2021
DOI: 10.26477/jbcd.v33i4.3016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coating Zirconium Implant Material with Nanoparticles of Faujasite

Abstract: Aim: To evaluate the wettability and microhardness of Zirconium (ZrO2) dental material when coated with different concentrations of Faujasite. Materials and methods: 30 circular disks produced from ZrO2, then each group is classified into 10 control groups, 10 coated groups with 3% Faujasite, and 10 coated groups with 7% faujasite by electro-spun tool to study variable properties in hardness and water contact angle of implant materials. Results: This study stated the high hardness in 7% of faujasite concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…72 However, this finding agrees with studies on zirconia implants that reported decreased water contact angle with increased ceramic material in the polymer coating. 73 The correlation between roughness and wettability is that increasing the surface's roughness will increase wettability (decrease the contact angle) due to the surface's chemistry. 74 The property of hydrophilicity has drawn more attention as a factor influencing the osseointegration of dental implants.…”
Section: Resultsmentioning
confidence: 99%
“…72 However, this finding agrees with studies on zirconia implants that reported decreased water contact angle with increased ceramic material in the polymer coating. 73 The correlation between roughness and wettability is that increasing the surface's roughness will increase wettability (decrease the contact angle) due to the surface's chemistry. 74 The property of hydrophilicity has drawn more attention as a factor influencing the osseointegration of dental implants.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the practicality and feasibility of the proposed EGCG-coating technique should be evaluated. The electrospray method employed in this study offers precision and control over the coating process [ 48 , 49 ], and it is the first time to be used with EGCG in any substrate. Additionally, the potential release of EGCG over time and its impact on the surrounding tissues should be explored as this technique is traditionally used as a drug delivery method which may increase the benefits of using EGCG on the surrounding bone [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Natural or synthetic polymers, ceramics and their composite materials have been widely used as biomaterials, most frequently employed for building scaffolds and implant coating materials that support the formation of bone tissue. [3][4][5][6] Synthetic biodegradable polymers find numerous applications in the field of biomedicine, while biopolymers are desirable materials for biomedical implants due to their high bioactivity, non-toxicity and resorbability properties. Furthermore, polymers can be considered 'smart' materials that have gained popularity as polymer coatings in various applications, such as corrosion resistance, surface functionalisation, wear resistance, enhancement of bioactivity and even switchable smart materials.…”
Section: Introductionmentioning
confidence: 99%
“…Natural or synthetic polymers, ceramics and their composite materials have been widely used as biomaterials, most frequently employed for building scaffolds and implant coating materials that support the formation of bone tissue. 3 6 …”
Section: Introductionmentioning
confidence: 99%